Pelatihan Pemasaran untuk UMKM : Meningkatkan Daya Saing Produk melalui Branding dan Promosi di Tajaul Karomah Desa Situ Gadung Kabupaten Tangerang - Andalusi, Ratih; Sulistiani, Sinta; Wulansari, Retno (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a vital component of Indonesia’s economic structure, particularly in rural areas. However, many MSME actors still face challenges in marketing their products effectively, especially in terms of branding and promotion. This community service (PKM) activity titled